2018
DOI: 10.1007/s10067-018-4291-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate, causes of death, and risk factors in systemic sclerosis: a large cohort study

Abstract: To investigate the clinical pattern, survival rate, causes of death and risk factors in a large cohort of Chinese Han patients with systemic sclerosis (SSc). Inpatients treated from 2002 to 2014 were included in this study. Patients were classified into diffuse cutaneous SSc (dcSSc), limited cutaneous SSc (lcSSc), and SSc-overlap syndrome groups. Data were analyzed using Chi-squared tests, Kaplan-Meier curves, log-rank tests, and Cox proportional hazards modeling. Among a total of 201 patients, dcSSc (50.2%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 21 publications
9
38
1
Order By: Relevance
“…Our overall survival rates at 1 year, 3 years, 5 years, 10 years were consistent with those reported previously [8,9,11,15,18]. In addition, we have shown a non-significant higher mortality rate from the diffuse cutaneous sub-type vs. the limited cutaneous sub type and the sine scleroderma sub type of SSc, in line with the published literature [8,11,12,16,17,[50][51][52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our overall survival rates at 1 year, 3 years, 5 years, 10 years were consistent with those reported previously [8,9,11,15,18]. In addition, we have shown a non-significant higher mortality rate from the diffuse cutaneous sub-type vs. the limited cutaneous sub type and the sine scleroderma sub type of SSc, in line with the published literature [8,11,12,16,17,[50][51][52].…”
Section: Discussionsupporting
confidence: 92%
“…However, 46.4% of the deaths in our cohort were directly attributable to SSc. Our results were consistent with the data from the EUSTAR cohort, finding that nowadays the two main causes of SSc-related were ILD and PH [3,6,12,15,17,50,51,60]. SSc GI-related mortality were frequent in our cohort (18.2%) and this cause of death represented 7.6% of deaths in metanalysis of Rubi-Rivas et al [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pooled SSc‐ILD prevalence was 56% (95% CI 49‐63) (Figure 2), which was stable in the sensitivity analysis (Figure 3). 11‐37 Heterogeneity across studies was high ( I 2 = 96.1%). There were significant differences in the prevalence of SSc‐ILD for subgroups stratified by region, study quality, SSc classification criteria, and publication year (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Cannon et al [7] found that up to 50% of asymptomatic patients have clinical markers indicative of renal dysfunction, such as proteinuria, an increased creatinine concentration, or hypertension. Various studies suggest a strong association between renal involvement and worse patient outcomes in SSc [3, 8]. In addition, a multinational SSc inception cohort study found renal crisis to be one of the predictors of early mortality in SSc patients [9].…”
Section: Introductionmentioning
confidence: 99%